Optimizing Agricultural Sustainability: Integrating Solar-Powered Drip Irrigation in the Onion-Corn Cropping System for Climate-Resilient Farming in Magsaysay, Occidental Mindoro - Declaro-Ruedas, Mary Yole Apple; Ruedas, Emmanuel G. (Discoveries in Agriculture and Food Sciences, 2024)
The study aims to determine the comparison of the yield response of bulb onion and Magenta corn using solar-powered automated drip irrigation and farmers’ practice (furrow) irrigation as a response to the deficit water supply brought by climate change. The experiment was conducted last December 2022 to August 2023 at Sitio Cabag, Brgy. Poblacion, Magsaysay, Occidental Mindoro. The Complete Randomized Design (CRD) of the experiment was adopted consisting of two treatments and five replicates. This was done by following the simple random sampling of assigning the treatments on the experimental plots (1000 sq meters). The Philippine National Standard for onion and corn production was followed. The same care and management practices were employed except for the type of irrigation used. Results show that drip irrigation resulted in reduced water consumption when irrigating an area of 1000 square meters, in comparison to furrow irrigation. Furthermore, the bulb onions, and magenta corn that were subjected to solar-powered drip irrigation exhibited greater fresh and dry weight, highest number of corn cob and grain weight. The T-test reveals a statistically significant difference between the treatments. Although, solar irrigation systems often entail more initial investment compared to furrow irrigation systems, it still offers greater advantage of lower maintenance and operation expenses. Lastly, this climate smart technology can minimize the cost on fuel expenditure and effectively maximize water scarce resources that could help mitigate climate change.